Gelombang Ekonomi Ke Empat, Gelombang Ide dan Gagasan - SUTANTO, M. HIMAWAN (Komunikator, 2014)
This paper attempts to analyze the development of creative economy in Indonesia. The main substance of this paper is based on the development of democracy that provides fresh air for the creativity. The key of creativity itself is the idea that is treated well. It especially happens in democratic countries. In the context of democracy, the idea can develop fast and get high appreciation. Idea is a new force which is capable to develop the world economy. For a long time, people had been thinking that product was the main capital of the economy. Creative industries will thrive with the assurance of a healthy and proper democracy. Keywords: Idea, Creative Industries